Electron Beam Effects on Oxide Thin Films—Structure and Electrical Property Correlations. (June 2019) - Neelisetty, Krishna Kanth; Mu, Xiaoke; Gutsch, Sebastian; Vahl, Alexander; Molinari, Alan; von Seggern, Falk; Hansen, Mirko; Scherer, Torsten; Zacharias, Margit; Kienle, Lorenz; Chakravadhanula, VS Kiran; Kübel, Christian
Abstract: In situ transmission electron microscope (TEM) characterization techniques provide valuable information on structure–property correlations to understand the behavior of materials at the nanoscale. However, understanding nanoscale structures and their interaction with the electron beam is pivotal for the reliable interpretation of in situ / ex situ TEM studies. Here, we report that oxides commonly used in nanoelectronic applications, such as transistor gate oxides or memristive devices, are prone to electron beam induced damage that causes small structural changes even under very low dose conditions, eventually changing their electrical properties as examined via in situ measurements. In this work, silicon, titanium, and niobium oxide thin films are used for in situ TEM electrical characterization studies. The electron beam induced reduction of the oxides turns these insulators into conductors. The conductivity change is reversible by exposure to air, supporting the idea of electron beam reduction of oxides as primary damage mechanism. Through these measurements we propose a limit for the critical dose to be considered for in situ scanning electron microscopy and TEM characterization studies.